Use of a generative chatbot as a middleman to improve User Experience in Interactive Fiction games - Dotta, Adriano Tolfo; Thielo, Marcelo Resende; Cheiran, Jean Felipe Patikowski (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2023)
In the 1970s and 1980s, interactive fiction games emerged and changed the gaming world by enabling players to talk to the machine, make their own decisions, choose their paths, and decide what to collect and do. This freedom captivated players, but at the time, games were limited by programmed scripts that only accepted words present in the game’s code dictionary in a limited format, usually two or three keywords by phrase. However, technological advances have paved the way for improvements in this regard, replacing scripts with artificial intelligence using APIs, such as ChatGPT, for example. Thus, it may be possible to offer players an even more natural and customized experience, where each decision is more flexible with the player’s writing style. In this work, we carried out a communication experiment with the ChatGPT as an intermediary for interactive fiction games and the Frotz game interpreter (a modified version of the Z-Machine interpreter) to assess the feasibility of the approach.